Design and fabrication of steering system for electric go kart - Muhammad Ikhwan, Razak (2012)
The objective of this project is to design and fabricate the steering system for electric go kart. Usually, majority of the go kart available at the market are based on petrol engine. The functional for this steering system are based on available product which is evaluated by research on the available source such as Internet. The basic part for the steering system such as steering column, track rods and stub axle are being research thoroughly to understand the function of each part. Before the fabrication process, some research for the milling, lathing, drilling and welding process are done to make sure it is suitable for the material used. To obtain the best designs, it has to be parallel with the scope of the project and suited with the criteria needed. Three concepts design are generated and final design are choose based on the Evaluation Table and discussion between team members and supervisor. Material selection is chose by surveying the available raw material from the store. Materials based on mild steel are choose due to its characteristic which can be weld and fabricate easily. Measuring, cutting, drilling, turning, milling, bending, welding, grinding and finishing process are done to complete this project. The final phase of this project is to assemble all the components and parts of the electric go kart fabricate from the team members. The purpose of this project is to allow the driver of go kart to change the direction during handling.